2021
DOI: 10.1002/asna.202113883
|View full text |Cite
|
Sign up to set email alerts
|

Black hole in asymmetric cosmological bounce

Abstract: We determine the causal structure of the McVittie spacetime for a cosmological model with an asymmetric bounce. The analysis includes the computation of trapping horizons; regular, trapped, and antitrapped regions; and the integration of the trajectories of radial null geodesics before, during, and after the bounce. We find a trapped region since the beginning of the contracting phase up to shortly before the bounce, thus showing the existence of a black hole. When the universe reaches a certain minimum scale … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 22 publications
(21 reference statements)
0
4
0
Order By: Relevance
“…Once in the expanding phase, its size begins to increase proportionally to the square of the scale factor. This is not the case in the McVittie spacetime [12,13], where the black hole horizon merges with the cosmological horizon in the contracting phase before reaching the bounce. Such a solution, however, does not take into account the coupling of the black hole with the cosmic dynamics, as in the present work.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Once in the expanding phase, its size begins to increase proportionally to the square of the scale factor. This is not the case in the McVittie spacetime [12,13], where the black hole horizon merges with the cosmological horizon in the contracting phase before reaching the bounce. Such a solution, however, does not take into account the coupling of the black hole with the cosmic dynamics, as in the present work.…”
Section: Discussionmentioning
confidence: 95%
“…We showed that although the metric describes a black hole in the past of the bounce, the trapping horizon disappears close to it, when it merges with the cosmic horizon. This result remains valid even when the bounce is not symmetric [13]. If the black hole interacts with the cosmic fluid, however, the McVittie metric is not an adequate description of the situation because in such metric the central mass remains constant.…”
Section: Introductionmentioning
confidence: 84%
“…Previous studies of black hole-cosmological bounces have either constructed initial data for black hole bouncing solutions [32], worked in a perturbative limit [33][34][35][36], or made use of analytic solutions (e.g. generalizations of the McVittie solutions [37][38][39]), that are limited by the fact that the metric evolution is prescribed ad-hoc, and from that the implied matter type and evolution is derived. The question of what happens to a black hole in a nonsingular cosmological bounce is particular salient for several reasons.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies of black hole-cosmological bounces have either constructed initial data for black hole bouncing solutions [34], worked in a perturbative limit [35][36][37][38], or made use of analytic solutions (e.g. generalizations of the McVittie solutions [39][40][41]), that are limited by the fact that the metric evolution is prescribed ad-hoc, and from that the implied matter type and evolution is derived. The question of what happens to a black hole in a nonsingular cosmological bounce is particular salient for several reasons.…”
Section: Introductionmentioning
confidence: 99%